Spasm of left main coronary artery. Issue 1 (January 1976) - Tzivoni, D; Merin, G; Milo, S; Gotsman, M S
Abstract : A 46-year-old male patient with atypical angina pectoris appeared to have an important elongated stenosis of the left main coronary artery on coronary arteriography, and slight irregularities in the left anterior descending, circumflex, and right coronary arteries. A saphenous vein bypass graft to the left anterior descending artery was performed, and this relieved the patient's symptoms. Postoperative coronary arteriography demonstrated a widely patent left main coronary artery and graft. The original narrowing of the left main coronary artery was probably caused by spasm and the source of the patient's anginal symptom.